Does Corruption Increase the risk Premium on the West African Economic Monetary Union (WAEMU) Bond Market? - MBENGUE, Mohamed Lamine (Information Management and Business Review, 2013)
We study the relationship between corruption and risk premium in West African Economic Monetary Union (WAEMU) market bond. Our sample consists of bonds through a public offering and private placement. For this research data was collected from the stock exchange (Bourse Régionale des Valeurs Mobilières). Number of bonds, average corruption and average spread analysis was used to analyze the data. Most country in WAEMU states has a corruption index below 3.5. The results show that corruption score has negative effects on economic performance indicators and there was a predominance of private placement debt relative to debt through a public offering.